IGF2BP3 (IMP3) expression in angiosarcoma, epithelioid hemangioendothelioma, and benign vascular lesions - Misuzu Okabayshi (Diagnostic Pathology, 2020)
Abstract Background Insulin-like growth factor-2 messenger RNA-binding protein 3 (IGF2BP3 or IMP3) is an oncofetal protein that is expressed in various cancer types, and its expression is often associated with poor prognosis. IGF2BP3 expression has not been fully settled in vascular lesions. Methods We evaluated the expression of IGF2BP3 in malignant (angiosarcoma and epithelioid hemangioendothelioma [EHE]) and benign (hemangioma, granulation tissue cappilaries, and pyogenic granuloma) vascular lesions using immunohistochemistry. IGF2BP3 expression was scored as negative (0% of endothelial/neoplastic cells), equivocal (1–25%), or positive (> 26%). Results Eight of 30 (26.7%) cases of angiosarcoma and two of five (40%) cases of epithelioid hemangioendothelioma were positive for IGF2BP3. In contrast, hemangiomas (10 cases) and granulation tissue capillaries (12 cases) were all negative for IGF2BP3, and some cases of pyogenic granuloma (six of 14 cases) was scored as equivocal. In angiosarcoma, IGF2BP3 expression was independent of age, gender, location, morphological pattern, prognosis, presence of metastatic foci, and PD-L1 expression. Conclusions IGF2BP3 is a useful marker to distinguish between malignant and benign vascular lesions.